Activation of the Intrinsic Pathway of Coagulation in Children with Meningococcal Septic Shock - Wuillemin, Walter A; Fijnvandraat, Karin; Derkx, Bert H F; Peters, Marjolein; Vreede, Willem; ten Cate, Hugo; Hack, C Erik (Thrombosis and Haemostasis, 1995)
Meningococcal septic shock (MSS) is complicated by activation of coagulation, fibrinolytic, and complement systems. We studied the contact system of the intrinsic pathway of coagulation in thirteen children with MSS. Activation was assessed upon admittance to the intensive care unit and 48 h thereafter, based on the measurement of factor XII- (FXII), prekallikrein- and factor XI (FXI) antigen levels, as well as on the detection of FXIa-FXIa inhibitor, FXIIa-C1-inhibitor, and kallikrein-C1-inhibitor complexes, respectively. Levels of FXII, prekallikrein and FXI were reduced to about 50% in all patients on admission, and were significantly higher 48 h later. FXIIa-C1-inhibitor complexes were elevated in 7 patients, and kallikrein-C1-inhibitor complexes in 2 patients. FXIa-α1-antitrypsin complexes were elevated in all patients, FXIa-C1-inhibitor complexes in nine, and FXIa-anti-thrombin III complexes in one patient. We conclude that patients with MSS have activation of the contact system, which may contribute to activation of coagulation, and thus to morbidity and mortality.